The implementation of Islamic values in mathematics education / Che Haslina Abdullah ... [et al. ] - Abdullah, Che Haslina; Ahmad, Nurfahiratul Azlina; Meor Hissan, Wan Syakira; Taha, Mohd Marbawi (2012)
Secularism which began in Italy during the 15th century has given big impact to Muslims in the field of Mathematics education. Up till now, the teaching of Mathematics is based on secular philosophy which neglects spiritual elements. Thus, Mathematics curriculum should be revised by implementing Islamic values, so these can be applied by students at an early age. This paper presents the five examples in mathematical knowledge of the number "1", the fractions, the optimization, the concept of "Hexagon" and diagram "Venn". Thus, the application of Islamic Mathematics is important to produce mathematicians who have faith in Allah SWT.